Catalyst-proximity protein chemical labelling on affinity beads targeting endogenous lectins. Issue 88 (18th October 2019) - Tsushima, Michihiko; Sato, Shinichi; Niwa, Tatsuya; Taguchi, Hideki; Nakamura, Hiroyuki
Abstract : Catalyst-proximity labelling on affinity beads enables the identification of ligand-binding proteins such as lectins, which cannot be analyzed by conventional techniques. 1-Methyl-4-arylurazole (MAUra) efficiently labels proteins bound to the beads. Abstract : Magnetic affinity beads functionalized with lactose and ruthenium/dcbpy complexes were developed. Using MAUra, a catalyst-proximity labelling reagent, the catalytic labeling of lactose-binding proteins was achieved with high selectivity on the beads. The first unbiased identification of cellular endogenous lectins bound to lactose (galectin-1 and galectin-3) was achieved with chemical labelling on the affinity beads.